Stakeholders Exsposition of Knowledge And Practice on Male Youth Football Programs In Addis Ababa: In View of Long Term Sport Development - Abebe Weldeyesus, Shewangizaw; Bekele Tola, Zeru; Yitbarek Wubshet, Berket (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2024)
Modern soccer calls for better understanding, spirit, and attentiveness on the part of all involved in the business. This reinforces that stakeholders are well-versed and practice based on the facts. This in turn helps them extend unrelenting support during critical ages and stages in the process of long-term soccer player development. In achieving youth sport developmental goals having well formulated model is very crucial. In light of this, through purposeful identification of participants, this study attempted to assess understanding of coaches, administrators, players and parents and academicians. The sight of the study was Addis Ababa. The participants account on their knowledge and knowledge based practices related to models in youth soccer development programs. This study adopted a mixed research design. A total of 80 male youth soccer players and 80 families were taken as sample to fill out the questionnaire. In addition to these four academicians, 6 youth soccer coaches and 3 administrative workers were interviewed. Mean, standard deviation and spearman correlation were employed to analyze quantitative data. The qualitative data were analyzed and organized thematically. Following the analysis it was found, comprehension of facts and related practices to model in long-term youth soccer development was recognized by those who have academic background in sport science, some coaches and an administrator. On the other hand, it was observed, remaining administrators, some coaches, and majority of parents and players were found to have a disconnected and insignificant knowledge on models of youth soccer development and related practices.